Pistacia atlantica rhizosphere characterization under arid climate - Lahoual M.; Belhadj S.; Nait Kaci Boudiaf M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The root environment is characteristic for each species, soil type and environmental condition. Interactions may be established between the roots and its environment, which influences the mineral nutrition and the relationship soil / plant. The importance of environmental characterization of Atlas pistachio root rhizosphere under arid climate is our primary objective in this work. The knowledge of the arid climates and their water and soil resources, that lead to vegetation in severe conditions, suggests the implementation of serious measures in plantations development in drylands. Our results confirmed these assumptions and revealed the presence and the extent of poor soils in these regions likely with arido-soils type, unsalty, limestone with very low organic matter content and low phosphorus rates. The richness of these soils in nitrogen, especially their rhizospheric fraction, may be explained by the root activity and the microbial biomass in the soil / root interface.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)